Psychological aspects of administrative activity of specialists of agencies and departments for emergency - Kremen’ Маркс; Gerasimchik Александр; Bogdanovich Алексей; Sergeev Всеволод (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The objectives, goals, elements of psychology in the system of control in a agencies and departments for emergency, psychological bases of the personality of head and styles of management are revealed. Much attention is paid to the factors of decision making of the leader of the agencies and departments for emergency, to the skills of conflict management in the team, to the improvement of management system and other important issues.